Study of antioxidant activity of liposomal forms of quercetin and curcumin in ischemic heart disease - Daria Pylypenko; Tatiana Gorbach; Yuriy Krasnopolsky (BioTechnologia, 2021)
Quercetin and curcumin are plant polyphenolic antioxidants with proven pharmacological efficacy. Their use is, however, limited due to low bioavailability and oral administration route. The encapsulation of lipophilic compounds in liposomes enables to increase their bioavailability and to create an injectable form. The present study aimed to comparatively investigate the antioxidant activity of a complex liposomal preparation containing two lipophilic antioxidants (quercetin and curcumin) and their monopreparations in liposomal forms. This study was conducted on Wistar line rats with experimental model of ischemic heart disease. Oxidative stress markers such as total antioxidant activity, malondialdehyde, and peroxidized proteins were analyzed in blood serum and cardiac tissue. Ischemic heart disease is accompanied with lipid peroxidation and changes in the activity of the antioxidant system. The obtained results demonstrated the antioxidant activity of monopreparations of curcumin and quercetin and their complex in liposomal forms. Quercetin and curcumin showed different antioxidant activities in terms of oxidative stress markers. The complex of the two antioxidants showed the synergistic effect of their lipophilic compounds in liposomal forms, which led to the normalization of test parameters according to the level of the control sample.